Assessment of the genetic diversity in Argentine rice cultivars with SSR markers - Giarrocco, Laura Estela (2007)
Genetic diversity of rice (Oryza sativa L.) cultivars that are historically significance to rice breeding and production in Argentina were evaluated at the DNA level. Sixty-nine accessions were surveyed with 26 simple sequence repeat (SSR) markers revealing the genomic relationship among cultivars. A total of 219 polymorphic bands were detected. Cluster analysis based on pair-wise comparisons of cultivar genetic similarities resolved the O. sativa accessions into two major O. sativa groups, indica and japonica, and the japonica group into the subgroups, tropical and temperate. These clusters agree with the pedigree information available on the accessions and almost all Argentina-released cultivars grouped within the japonica cluster. Application of DNA polymorphism analysis revealed genomic relationships in Argentine rice germplasm, generating a database useful for cultivar identification, local germplasm conservation, and breeding programs.